2012
DOI: 10.1088/1751-8113/45/9/095305
|View full text |Cite
|
Sign up to set email alerts
|

Moment-based evidence for simple rational-valued Hilbert–Schmidt generic 2 × 2 separability probabilities

Abstract: Employing Hilbert-Schmidt measure, we explicitly compute and analyze a number of determinantal product (bivariate) moments |ρ| k |ρ P T | n , k, n = 0, 1, 2, 3, . . ., P T denoting partial transpose, for both generic (9-dimensional) two-rebit (α = 1 2 ) and generic (15-dimensional) two-qubit (α = 1) density matrices ρ. The results are, then, incorporated by Dunkl into a general formula (Appendix D 6), parameterized by k, n and α, with the case α = 2, presumptively corresponding to generic (27-dimensional) quat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(128 citation statements)
references
References 67 publications
5
122
0
1
Order By: Relevance
“…[40]). Proofs are certainly still lacking for the interesting generalized Bloch radii/Casimir invariants conjectures made above, as well as those in a number of other recent reports [11][12][13][14]20,22,36] and the infinite summation formula given above (1)(2)(3).…”
Section: Qubit-qutrit Analyses With Random Induced Measurementioning
confidence: 94%
See 1 more Smart Citation
“…[40]). Proofs are certainly still lacking for the interesting generalized Bloch radii/Casimir invariants conjectures made above, as well as those in a number of other recent reports [11][12][13][14]20,22,36] and the infinite summation formula given above (1)(2)(3).…”
Section: Qubit-qutrit Analyses With Random Induced Measurementioning
confidence: 94%
“…In regard to these matters, a diverse body of evidence-though yet no formal proofhas been developed, strongly indicating that the probability that a two-qubit state is separable/disentangled/classically correlated, that is, expressible as the convex sum of products of qubit states [10], is 8 33 ≈ 0.242424 [11][12][13][14]. The measure employed in the underlying computations was the familiar Hilbert-Schmidt (Euclidean/flat) one [2,15], while the integration of this measure was conducted over the standard 15-dimensional convex set of 4 × 4 (Hermitian) density matrices.…”
Section: Introductionmentioning
confidence: 99%
“…This decomposes into the sum of the Lovas-Andai separability functions 1 20 ε 2 (ε 4 − 6ε 2 + 15) and and qubit-qudit states, among others, examined above. But, given that the Hilbert-Schmidt separability probability of 8 33 for the 15-dimensional convex set of two-qubit states has itself proved highly formidable to well establish [1,[4][5][6][7][8][9][10] (though not yet formally proven), it seems that major advances would be required to achieve such a goal in these still higher-dimensional settings (and, thus, confirm or reject the conjectures above). Implicit in the analytical approach pursued here has been the clearly yet unverified assumption that the separability/PPT-probabilities will continue to be rational-valued for the higher-dimensional systems, as they have, remarkably, been found to be in the 4 × 4 setting.…”
Section: E Extended Master Formula Investigationmentioning
confidence: 99%
“…One of our goals here has been to determine if we could use the N = 4 results [1,[4][5][6][7][8][9][10] to gain insight into the N > 4 counterparts, and, more specifically, if certain analytical properties continue to hold. We found some encouragement for undertaking such a course from the research reported in [30].…”
Section: A Casimir Invariantsmentioning
confidence: 99%
“…To obtain the new formulas ( , ) to be presented here for the separability probability amounts for which | PT | > | | holds, we first employed-as in our prior studies [1,9,16,17]-the Legendre-polynomial-based probability density-approximation (Mathematica-implemented) algorithm of Provost [18] (cf. [19]).…”
Section: Previous Analysesmentioning
confidence: 99%